[Naval Flight Preparatory School group portrait]
Back Row, left to right: Nick Hyman, engineer; Frank Pungerear, radio operator, Red Teepe, armorer gunner; Bill Young, Ball turret; Ralph Kitterman, upper local. Front Row left to right: Wm. Partridge, 1st pilot; Jay Cochran, 2nd pilot; Earle Robinson, Navigator; Donald Day, Bombardier.